Current Issues of International Legal Regulation of the Convergence of Transport and Logistics Systems within the EAEU - M. A. Drozdova (Евразийская интеграция: экономика, право, политика)
With the development of integration processes on the territory of the Eurasian Economic Union, the convergence of transport and logistics systems is a  necessary condition for both transport connectivity and the development of trade relations. The current geopolitical situation, which led to an increase in traffic and within the EEU and the redirection of transport flows to the East, requires a change in  the paradigm of the legal regulation of the transport industry at the interstate level.Aim . Reveal the main problems of international legal regulation of the convergence of transport and logistics ecosystems in the Eurasian region.Tasks. It is proposed to consider the main trends of the formation of an array of legal regulation of the transport and logistics industry in the EAEU as part of the implementation of a  common transport policy and the implementation of major infrastructure projects, such as the Eurasian transport framework, to analyze the relevance of the main EAEU documents in the field of transport and logistics, to present the basic elements of the new paradigm of the EAEU unified transport system, including railway transport.Methods. When conducting the research, comparative-legal, formal-legal methods, synthesis, deduction, induction, as well as abstraction and the systematic method were used.Results . The necessity of a   significant change in the approach to the formation of an effective model of international legal regulation of transport integration within the EAEU, clarification of the main directions of a common transport policy of the member states of the association, ensuring its competitiveness at the world level, transport and technological sovereignty of Russia and other partner countries, full realization of the transit potential of the union, as well as the effective functioning of the industry in the conditions of Industry 4.0 is substantiated.Conclusions . The proposed integrated approach will make it possible to fully implement the adopted Strategic Directions for the development of Eurasian economic integration until 2025, to lay the foundations for a   new stage of integration of transport and logistics systems within the EAEU with the achievement of the set significant milestones in the interests of the countries and peoples of our integration association.